Process Evaluation of the Type 2 Diabetes Mellitus PULSE Program Randomized Controlled Trial: Recruitment, Engagement, and Overall Satisfaction - Aguiar, Elroy J. (Am J Mens Health, 2017)
Background: Men are underrepresented in weight loss and type 2 diabetes mellitus (T2DM) prevention studies. Purpose: To determine the effectiveness of recruitment, and acceptability of the T2DM Prevention Using LifeStyle Education (PULSE) Program—a gender-targeted, self-administered intervention for men. Methods: Men (18–65 years, high risk for T2DM) were randomized to intervention (n = 53) or wait-list control groups (n = 48). The 6-month PULSE Program intervention focused on weight loss, diet, and exercise for T2DM prevention. A process evaluation questionnaire was administered at 6 months to examine recruitment and selection processes, and acceptability of the intervention’s delivery and content. Associations between self-monitoring and selected outcomes were assessed using Spearman’s rank correlation. Results: A pragmatic recruitment and online screening process was effective in identifying men at high risk of T2DM (prediabetes prevalence 70%). Men reported the trial was appealing because it targeted weight loss, T2DM prevention, and getting fit, and because it was perceived as “doable” and tailored for men. The intervention was considered acceptable, with men reporting high overall satisfaction (83%) and engagement with the various components. Adherence to self-monitoring was poor, with only 13% meeting requisite criteria. However, significant associations were observed between weekly self-monitoring of weight and change in weight (r(s) = −.47, p = .004) and waist circumference (r(s) = −.38, p = .026). Men reported they would have preferred more intervention contact, for example, by phone or email. Conclusions: Gender-targeted, self-administered lifestyle interventions are feasible, appealing, and satisfying for men. Future studies should explore the effects of additional non-face-to-face contact on motivation, accountability, self-monitoring adherence, and program efficacy.